Analysis of strategic programs in planning and developing cocoa agribusiness in Bantaeng Regency - Andi Nuddin; Rio Akbar Rahmatullah; Arsyad, Muhammad; Jamil, Muh Hatta; Madung, Nurfaaidah; Amran, Arman (Anjoro: International Journal of Agriculture and Business, 2023)
The fluctuation of production levels, low innovation adoption rates, and low cocoa prices at the farm level are important problems in cocoa agribusiness that cannot be allowed to prolong, especially in production centers such as Bantaeng Regency, South Sulawesi Province. The purpose of this research is to provides strategic program recommendations as a reference for policymakers in designing cocoa agribusiness planning and development. This research used Interpretative Structural Modeling (ISM) analysis to be able to formulate a complex policy structure based on elements and formulate a hierarchy of relationships between elements. The results show that there are five key programs in planning and developing cocoa agribusiness in Bantaeng Regency, namely effectiveness of extension in the field, capacity building of extension workers, the establishment of farming partnerships with companies, the establishment of specialized cocoa development team, and guarantee of price stability. These key programs need to be assisted by supporting programs such as institutional development programs, effective coordination between institutions, effective technology transfer to farmers, provision of organic technology, providing rewards for farmers, providing access to capital, strengthening digital marketing, and improving cocoa quality through fermentation. Based on the interpretation of this research, stakeholders need to have an understanding of the priorities and synergy between programs to ensure the development of cocoa agribusiness that is right on target and in accordance with the needs and conditions currently faced.